Temple of Aphaia at Aegina
Closer view of interior colonnade with exposed end of architrave showing grooves for lifting block into place. Bernini was given commission by Alexander VII himself, but serious work was not begun until after the Pope's death. Plans during the reign of Alexander's successor, Clement IX, called for erection of this tomb in the choir of S. Maria Maggiore, which was to have been transformed according to plans by Bernini. This scheme was not carried out, and after the death of Clement IX the concept was abandoned and an appropriate place in St. Peter's decided upon. The location is above the door of the Porta di S. Marta, just west of the left transept. For this great collaborative effort of his studio, Bernini completed the drawings and model in 1672. Among the many people who contributed, the most important were Giulio Cartari (noted 1665-78), who did the allegories of Truth, Prudence and Justice, Michele Maglia (noted 1657, died 1700), who was responsible for the figure of the Pope, and Giuseppe Mazzuoli (1644-1725), who executed the Charity. Work was esesntially completed in 1678.